A NONLINEAR ANALYSIS OF MONETARY POLICY WITH DOMINANCE INDICES IN TURKEY: MS-VAR APPROACH - Ersin, Ozgur; Bildirici, Melike (INST ECONOMIC FORECASTING, 2017)
The study focuses on analyzing the policies followed in Turkey based on inflation targeting with an application of interest rate corridor policy in which the spread between the two policy rates, namely, the borrowing and lending rates. To overcome the difficulty of two different policy rates, two indices, the PDI and the MDI are utilized to capture the response of the monetary authority within a nonlinear Taylor rule context. The empirical findings for the Turkish economy with MS-VAR and MS-Granger causality analyses suggest that while the policy interest rates are determined in the spirit of the Taylor rule, the monetary policy involuntarily affirms inflation after the application of the policy, a finding that is consistent with the FTPL theory. As a result, as the central bank tries to establish price stability and financial stability with two policy interest rates, accepting higher inflation rates could be unavoidable. The results also are in favor of bi-directional nonlinear causality which led to important policy implications.
Keywords: inflation targeting; Taylor rule; nonlinear econometrics; Markov-switching; Granger causality; RATE PASS-THROUGH; FINANCIAL CRISIS; EURO AREA; CAUSALITY; RATES; Business & Economics